2014
DOI: 10.1159/000367840
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-RhoA Signaling Pathways in Fluoride-Treated Ameloblast-Lineage Cells

Abstract: This study examined the effect of sodium fluoride (NaF) on the Wnt and RhoA signaling pathways in murine ameloblast-lineage cells (ALCs) to better understand the developmental mechanisms of dental fluorosis. Wnt and Rho pathway activities were investigated when ALCs were treated with 1.5 mM NaF, dickkopf-related protein-1 (Dkk-1), secreted frizzled related-protein-2 (sFRP-2), β-catenin siRNA dominant negative RhoA (RhoADN) plasmid and Y-27632. Wnt pathway activity was investigated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The levels of Wnt3a and Wnt5a, the canonical and non-canonical Wnt family proteins, significantly increased in response to NaF treatment [ 162 ]. It has also been confirmed that both Wnt and Rho pathways were upregulated by 1.5 mM NaF [ 163 ]. In addition, excessive fluoride intake (5–50 ppm F − ) in rats led to the stimulation of calpain-1 (a proteolytic enzyme), which was accompanied by a significant decrease in RhoA levels in the cytoplasm of hippocampal cells and a high increase in its expression in cell membranes [ 164 ].…”
Section: Mechanisms Of Drug Resistance In Glioblastomamentioning
confidence: 90%
“…The levels of Wnt3a and Wnt5a, the canonical and non-canonical Wnt family proteins, significantly increased in response to NaF treatment [ 162 ]. It has also been confirmed that both Wnt and Rho pathways were upregulated by 1.5 mM NaF [ 163 ]. In addition, excessive fluoride intake (5–50 ppm F − ) in rats led to the stimulation of calpain-1 (a proteolytic enzyme), which was accompanied by a significant decrease in RhoA levels in the cytoplasm of hippocampal cells and a high increase in its expression in cell membranes [ 164 ].…”
Section: Mechanisms Of Drug Resistance In Glioblastomamentioning
confidence: 90%
“…Research has indicated that uorosis can cause damage to the CNS by disrupting various signaling pathways, including NF-κB, 37 MAPK, 38 and Wnt. 39 We focused on the in ammatory response and only investigated NF-κB signaling. Other pathways should also be considered in future research.…”
Section: Discussionmentioning
confidence: 99%
“…We identified Ser675 of β‐catenin as a potential new target site for Rho/ROCK in the context of Wnt/β‐catenin pathway regulation. Rho/ROCK could modulate Wnt signaling by affecting DKK1 in ameloblast‐lineage cells, 61 while ROCKi downregulated DKK1 in TM cells.…”
Section: Discussionmentioning
confidence: 99%